2001
DOI: 10.1093/brain/124.5.974
|View full text |Cite
|
Sign up to set email alerts
|

Central nervous system disease in patients with macrophagic myofasciitis

Abstract: Macrophagic myofasciitis (MMF), a condition newly recognized in France, is manifested by diffuse myalgias and characterized by highly specific myopathological alterations which have recently been shown to represent an unusually persistent local reaction to intramuscular injections of aluminium-containing vaccines. Among 92 MMF patients recognized so far, eight of them, which included the seven patients reported here, had a symptomatic demyelinating CNS disorder. CNS manifestations included hemisensory or senso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(70 citation statements)
references
References 20 publications
0
68
0
2
Order By: Relevance
“…Our morphologic study results for the intradermal nerves obtained from affected limbs that showed endoneurial edema and selective degeneration of unmyelinated fibers coincided well with the findings mentioned above. One important disease that must be differentiated from CRPS-I in vaccinated patients is macrophagic myofasciitis (27,28). This disorder develops as an unusual reaction to the intramuscular injection of aluminium-containing vaccines and is characterized by common manifestations of diffuse myalgia and arthralgia, as well as elevated levels of serum CK and CRP.…”
Section: A B C Dmentioning
confidence: 99%
“…Our morphologic study results for the intradermal nerves obtained from affected limbs that showed endoneurial edema and selective degeneration of unmyelinated fibers coincided well with the findings mentioned above. One important disease that must be differentiated from CRPS-I in vaccinated patients is macrophagic myofasciitis (27,28). This disorder develops as an unusual reaction to the intramuscular injection of aluminium-containing vaccines and is characterized by common manifestations of diffuse myalgia and arthralgia, as well as elevated levels of serum CK and CRP.…”
Section: A B C Dmentioning
confidence: 99%
“…In consequence, the World Health Organization (WHO) Vaccine Safety Advisory Committee has recognized that there may be a subset of predisposed individuals who may be sensitive to Al adjuvants (Authier et al, 2001). Overall, there is good evidence that high levels of aluminum exposure can have adverse effects on human health.…”
Section: Transitory Exposure To High Levels Of Aluminum Can Results Inmentioning
confidence: 99%
“…Vaccines have been shown to stimulate the immune system and can cause chronic inflammation [21,22]. Vaccines have been shown to cause cortisol release [23][24][25][26][27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%